2012
DOI: 10.1136/fetalneonatal-2010-196451
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal stroke

Abstract: Neonatal stroke encompasses a range of focal and multifocal ischaemic and haemorrhagic tissue injuries. This review will concentrate on focal brain injury that occurs as a consequence of arterial infarction, most frequently the left middle cerebral artery, or more rarely as a consequence of cerebral sinus venous thrombosis (CSVT). Both conditions are multifactorial in origin. The incidence of both acquired and genetic thrombophilic disorders in both mothers and infants is high although rarely causal in isolati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
1
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 47 publications
(113 reference statements)
2
57
1
5
Order By: Relevance
“…Earlier studies have found that prothrombotic coagulation factors are present in more than half of neonatal main artery strokes, but it has been suggested that they likely play only a minor role in the pathogenesis of stroke. 11,20 In 2 patients, stroke was most likely related to arteriopathy. One of these patients had Miller-Dieker lissencephaly and the other idiopathic infantile arterial calcification.…”
Section: August 2013mentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies have found that prothrombotic coagulation factors are present in more than half of neonatal main artery strokes, but it has been suggested that they likely play only a minor role in the pathogenesis of stroke. 11,20 In 2 patients, stroke was most likely related to arteriopathy. One of these patients had Miller-Dieker lissencephaly and the other idiopathic infantile arterial calcification.…”
Section: August 2013mentioning
confidence: 99%
“…Placental disorders may be under-recognized in neonatal stroke because placentas are often not adequately examined or have been discarded before stroke becomes apparent. 11 We had data on placental abnormalities for only 15 mothers. More than half of them had placental abnormalities that could be regarded as a risk factor for developing stroke, specifically placental infarction, chorioamnionitis, and placental abruption.…”
Section: August 2013mentioning
confidence: 99%
“…Neonatal encephalopathy -be it manifested by seizures, abnormal tone, or altered level of consciousness -is known to be a common presenting feature of neonatal stroke. 22,23 Moreover, neonates with stroke do not usually require major caseroom resuscitation, a feature that is more common in neonates who have suspected birth asphyxia. 22,23 An Executive Summary by the American College of Obstetricians and Gynecologists' Task Force on Neonatal Encephalopathy stated that in the context of acute intrapartum hypoxic-ischemic events, '[the] developmental outcome is spastic quadriplegia or dyskinetic cerebral palsy' and that 'other subtypes of cerebral palsy are less likely.'…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Moreover, neonates with stroke do not usually require major caseroom resuscitation, a feature that is more common in neonates who have suspected birth asphyxia. 22,23 An Executive Summary by the American College of Obstetricians and Gynecologists' Task Force on Neonatal Encephalopathy stated that in the context of acute intrapartum hypoxic-ischemic events, '[the] developmental outcome is spastic quadriplegia or dyskinetic cerebral palsy' and that 'other subtypes of cerebral palsy are less likely.' 24 Our results support this element of the Executive Summary, since the majority (79%) of children with neonatal encephalopathy with suspected birth asphyxia had either a spastic quadriplegia or dyskinetic neurological subtype.…”
Section: Discussionmentioning
confidence: 99%
“…Both are associated with fetal risk factors such as prothrombotic disorders, systemic illness, and inflammation, as well as maternal and obstetric factors or birth complications. Sources of presumed emboli include placental fragments or clots, thrombi in involuting fetal vessels, and thrombi or air in punctured or catheterized vessels [3]. Notably, emboli from fetal or neonatal venous circulation can enter arterial circulation by passage across the patent foramen ovale, resulting in a thromboembolic event, scarcely also symptomatic after occluding a nonterminal arterial branch [4].…”
Section: Discussionmentioning
confidence: 99%